Translational Strategies to Eliminate Chronic Hepatitis B in Children: Prophylaxis and Management in East Asian Countries - Kang, Ben; Yi, Dae Yong; Choe, Byung-Ho (Frontiers in Pediatrics, 2022)
Translational medical research on hepatitis B virus (HBV) infection and chronic hepatitis B (CHB) pathogenesis provides guidance on strengthening the treatment and prevention strategies of CHB. Preventing vertical transmission is the key to eliminating HBV infection in children. The understanding of HBV replication, hepatocyte turnover, and the fate of covalently closed circular DNA (cccDNA) would help establish a personalized application of the guidelines, especially concerning the discontinuation of nucleos(t)ide analog (NA) treatment in children. Transplacental leakage of HBV-infected maternal blood is suggested as the leading cause of vertical transmission. Prenatal maternal prophylaxis could diminish maternal HBV viremia at delivery, to reduce the risk of neonatal HBV infection. The meaning of the expression “no additional risk of breast milk feeding” is thereby explained. Understanding the untreated natural course of CHB in children and the course changeable by treatment is important to apply individualistic strategies and avoid the immoral selection of treatment indications. NAs with potent efficacy and a high barrier to drug resistance should be used as first-line treatment to reduce the likelihood of NA-resistant HBV development because the rate of mutant HBV emergence might count on the infected hepatocyte turnover rate in chronic HBV infection. Although elimination of intranuclear cccDNA is difficult by NAs alone, a cure is possible by human immunity and hepatocyte turnover. The reduction of intranuclear cccDNA occurs after the destruction of HBV-infected hepatocytes, non-cytolytic immune response, apoptosis of hepatocytes, and compensatory cell proliferation. Therefore, consolidation therapy after NA-induced hepatitis B e-antigen seroconversion must be necessary for a sufficient period. This review also summarizes the treatment strategies of CHB in children based on the practical application of translational research.